Energy Prices between Beijing and Shanghai: Testing for the Long-run Equilibrium. (November 2016) - Zou, Gaolu; Wang, Jiquan
Abstract: This paper mainly aims to test the long-run relationship between Beijing and Shanghai energy prices. Panel cointegration tests indicate a cointegrating vector. Additionally, feedback was implied for the changes in Beijing and Shanghai energy prices. Therefore, empirical evidence supports the argument that similar macro fundamentals (supreme political power, considerable economic and population sizes) lead to the long-term equilibrium between energy markets. We suggest that the central government plays a leading role in regulating energy prices.